Fullerenol changes metabolite responses differently depending on the iron status of cucumber plants. - Nikolai P Bityutskii; Kirill L Yakkonen; Roman Puzanskiy; Kseniia A Lukina; Alexey L Shavarda; Konstantin N Semenov (PLoS ONE)
The unique properties of carbon-based nanomaterials, including fullerenol, have attracted great interest in agricultural and environmental applications. Iron (Fe) is an essential micronutrient for major metabolic processes, for which a shortage causes chlorosis and reduces the yield of many crops cultivated worldwide. In the current study, the metabolic responses of Cucumis sativus (a Strategy I plant) to fullerenol treatments were investigated depending on the Fe status of plants. Cucumber plants were grown hydroponically, either with [+FeII (ferrous) and +FeIII (ferric)] or in Fe-free (-FeII and -FeIII) nutrient solution, with (+F) or without (-F) a fullerenol supply. Iron species-dependent effects were observed in either Fe-fed or Fe-starved plants, with alteration of metabolites involved in the metabolism of carbohydrates, amino acids, organic acids, lipophilic compounds. Metabolic perturbations triggered by fullerenol in the FeIII-treated plants were in the opposite kind from those in the FeII-treated plants. Whereas in the FeIII-fed plants, fullerenol activated the metabolisation of carbohydrates and amino acids, in the FeII-fed plants, fullerenol activated the metabolisation of lipophilic compounds and repressed the metabolisation of carbohydrates and amino acids. In FeIII-deficient plants, fullerenol stimulated the metabolism of C3 carboxylates and lipophilic compounds while repressing the metabolism of amino acids, hexoses and dicarboxylates, while in FeII-deficient plants, activations of the metabolism of amino acids and dicarboxylates and repression of sterol metabolism by fullerenol were observed. The results indicated that the valence state of Fe sources is of importance for re-programming metabolome responses in cucumber to fullerenol either in Fe-sufficient or Fe-deficient conditions. These investigations are significant for understanding fullerenol interactions and risk assessment in plants with different Fe statuses.